Manajemen Risiko Keamanan Pangan Berbasis Halal: Analisis Titik Kritis Bahan Baku, Proses Produksi, dan Distribusi: Halal-Based Food Safety Risk Management: Critical Point Analysis of Raw Materials, Production Processes and Distribution - Andi Wawan Mulyawan; Nasrullah bin Sapa (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2026)
The food industry faces complex challenges in ensuring food safety and product halalness simultaneously. The globalization of supply chains, the diversity of raw materials, and the dynamics of production processes make the risk of contamination—whether biological, chemical, physical, or non-halal—increasingly high. This research aims to analyze critical points in the food supply chain, especially raw materials, production processes and distribution, as well as evaluating risk mitigation strategies based on the integration of the Halal Assurance System (HAS 23000) and Hazard Analysis Critical Control Point (HACCP). The research method uses literature studies through searching 2019–2024 journals, official regulations, and international standards related to food safety and halal certification. The study results show that the greatest risk to raw materials comes from high-risk ingredients that are difficult to verify visually and often have multi-source origins. In the production process, cross-contamination is a dominant risk that demands strict sanitation, process flow and facility segregation. Meanwhile, the distribution stage is vulnerable to product mixing, failure to maintain temperature, and weak traceability systems. The integration of HAS and HACCP is proven to provide a more effective and comprehensive risk mitigation framework, thus becoming a strategic approach to guarantee halalan-thayyiban products.